Women in Local Governance: Citizen Perceptions of Female Leaders’ Servant and Ethical Leadership and Their Citizenship Behaviors in Kathmandu, Nepal - Aryal, Bindu Tandon; Kaur, Kamaljeet (Journal of Advanced Academic Research, 2026)
The introduction of the reservation system in the local governance system of Nepal hassignifi cantly increased female representation in ward offices. This high number now offers avaluable opportunity to understand how citizens perceive the leadership behaviours of theseelected women. This study investigates how perceptions of citizens about Servant Leadership(SL) and Ethical Leadership (EL) of female ward representatives influence the OrganizationalCitizenship Behaviour of citizens with the Public Service Motivation (PSM) as a mediator. Usingsimple random sampling, data was collected from 458 residents of Gokarneshwor Municipality,Kathmandu filtering only those respondents who were familiar with the elected female wardleaders. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze thedata which showed strong explanatory power with 78.6% of variance in the citizens’ OCB (R² =0.786). Th e results revealed that direct effects of SL (β = 0.511, p < .001) and EL (β = 0.444, p